Dual liquidity crises under alternative monetary frameworks - Adalbert Winkler; Ulrich Bindseil (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
In a dual liquidity crisis, both the government and the banking sector are under severe funding stress. By nature, dual crises have the potential of being particularly disruptive and damaging. Thus, understanding their mechanics, how they unfold and how they can be addressed under various monetary and international financial regimes, is crucial. We capture the logic of a dual crisis through a new, rigorous approach. A closed system of financial accounts allows for a systematic comparative review of underlying liquidity shocks as well as built-in liquidity buffers, including their limits beyond which a credit crunch materializes. Based on this we are able to (i) make precise the otherwise vague interpretations of liquidity flows and policy options; (ii) compare capacities to absorb shocks under alternative international financial systems; (iii) explain how various constraints interact; (iv) draw lessons for achieving higher resilience against self-fulfilling confidence crises. Most importantly, we analyze the role of a number of potential constraints to an elastic central bank liquidity provision, namely the availability of central bank eligible assets, limits deliberately imposed on the central bank`s ability to lend to or purchase assets of banks and governments (including monetary financing prohibitions), and limits in a fixed exchange rate regime relating to the gold or foreign currency reserves of the central bank.
Keywords: E50; E58; E42; 330